2013
DOI: 10.1111/scs.12046
|View full text |Cite
|
Sign up to set email alerts
|

Family caregivers’ experiences of relinquishing the care of a person with dementia to a nursing home: insights from a meta‐ethnographic study

Abstract: Many people with dementia are cared for in their homes by family caregivers. As the dementia progresses, admission of the family member to a nursing home becomes inevitable. The aim of this meta-ethnographic study was to describe caregivers' experiences of relinquishing the care of a family member with dementia to a nursing home. A systematic literature search of PubMed, Cinahl and PsychInfo, between the years 1992 and 2012, was performed, and 10 qualitative articles, based on 180 family caregivers' experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
165
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(182 citation statements)
references
References 33 publications
15
165
0
2
Order By: Relevance
“…This finding supports studies of family burdens in general (Graneheim et al, 2014) and family burdens caused by workloads to compensate for discontinuity (cf. Bastawrous, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…This finding supports studies of family burdens in general (Graneheim et al, 2014) and family burdens caused by workloads to compensate for discontinuity (cf. Bastawrous, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…This process was reported to be accompanied by feelings of guilt, loss and shame (Graneheim et al, 2014). Such findings are reinforced by research investigating why couples living with dementia remain together (Loboprabhu et al, 2005;Davies, 2011).…”
Section: Staying Togethersupporting
confidence: 54%
“…Care partners have reported feeling guilty and struggling to adapt with their new lives post seeking care home placements for people with dementia that they have cared for (Garity, 2006;Graneheim et al, 2014 (Graneheim et al, 2014). Such findings are reinforced by research investigating why couples living with dementia remain together (Loboprabhu et al, 2005;Davies, 2011).…”
Section: Staying Togethermentioning
confidence: 61%
See 1 more Smart Citation
“…She found that relatives seemed to accept the inevitability of shortcomings in the home. Graneheim et al (2014) also found that family members would make excuses when they experienced poor quality care, often blaming poor education or lack of staff, or putting it down to an isolated incident. Many people see moving into a care home as a last resort and have negative perceptions of care homes, either based on personal experience or media portrayal (Davies and Nolan, 2003).…”
Section: Introductionmentioning
confidence: 99%